2021
DOI: 10.3390/ijerph182312659
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia, Obesity, and Ethnicity in Mexican Children

Abstract: The aim of this study was to assess lipid disorders in children from five ethnic groups, both urban and indigenous, from northern and central Mexico. We measured the lipid profile to determine the ability of the body mass index (BMI) to discriminate an abnormally high lipid level using receiving operating characteristics (ROC). We analyzed the association and interaction of obesity and ethnicity with lipid disorders using generalized linear models in 977 children. The highest prevalence of lipid disorders (hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…There is a close relationship between obesity and abnormal lipid metabolism. Many studies have revealed a close correlation between high BMI and abnormal lipid metabolism ( 32 , 33 ). In the present study, we found a significant association between high BMI and abnormal lipid metabolism only in female MDD patients with abnormal glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…There is a close relationship between obesity and abnormal lipid metabolism. Many studies have revealed a close correlation between high BMI and abnormal lipid metabolism ( 32 , 33 ). In the present study, we found a significant association between high BMI and abnormal lipid metabolism only in female MDD patients with abnormal glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is usually accompanied by dyslipidemias, i.e., alterations in lipid metabolism, such as hypercholesterolemia, hypertriglyceridemia, increased LDL-c, decreased HDL-c and increased circulating free fatty acids [ 61 , 62 ]. These complications increase the individual’s cardiometabolic risk; thus, addressing them is often carried out as part of an obesity treatment [ 63 ].…”
Section: Effects Of Naringenin Against the Various Components Of Obesitymentioning
confidence: 99%
“…[7,8] Lipids (mainly triglycerides) represent a major source of calories in most Western diets. [9][10][11] Lipids are mainly digested in the small intestine, duodenum and jejunum, [12,13] simultaneously using components secreted by the pancreas and gallbladder, such as bile salts and pancreatic enzymes. [12][13][14] The CCK peptide family has many functions, [15] it is important in regulating gallbladder contraction and pancreatic enzyme release.…”
Section: Introductionmentioning
confidence: 99%